O papel do profissional gerontólogo bacharel na percepção de outros profissionais da saúde de São Caetano do Sul, São Paulo - Mota, Cristiane Rodrigues [UNIFESP] (2018)
The population ageing is an undeniable reality. This phenomenon is due, among others, to the availability of a range of diagnostic and therapeutic technological resources focused on the disease prevention and health promotion. Alongside the technology, the training of professionals involved with the attention to health plays a key role, expanding the look on human aging. In this context, it has been created the career in Gerontology in Brazil, forming generalist professionals with a full and comprehensive view on the aging process. Since the first graduates formed in the year 2009, the career is in consolidation process, there are few professionals working in the labor market. In this sense, the aim of this study was to characterize the recognition of primary health care professionals about the gerontologist performance in the team, and to correlate the social recognition of the profession as a possible determinant of the professional insertion in the working team. For that purpose, interviews were carried out with professionals from the Center for Family Health Support and from a Basic Health Unit, linked to an Integrated Health and Education Center focused on the third age of São Caetano do Sul city. This city was chosen due it concentrates a large contingent of elderly individuals, for whom health care policies have historically been formulated. The results, recorded and subsequently transcribed, were objects of the analysis of content from the perspective of Laurence Bardin, being grouped together by similarity of meanings. It was observed that the interviewees had had little or no contact with the graduate in gerontology. Most of them were unaware of the functions and formation of the gerontologist, often confusing him with the figure of the doctor geriatrician. It was also observed a flagrant omission in the non-inclusion of a gerontologist in the health team, which, according to the participants themselves, could not only improve attention to the individuals served, but positively influence in their own view of the aging and care needed for the elderly.